2020
DOI: 10.1136/bmjresp-2020-000563
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and causes of death of patients with acute exacerbation of fibrosing interstitial lung diseases

Abstract: BackgroundThe aim of this study was to compare the clinical characteristics, causes of death and factors impacting on the prognosis of patients with idiopathic pulmonary fibrosis (IPF) and other fibrosing interstitial lung disease (FILD) with a history of acute exacerbation (AE) of IPF or FILD.MethodsRetrospective data of hospital treatment periods caused by AE-IPF and AE-FILD were collected from medical records. Clinical features and survival data of IPF and non-IPF cases were evaluated and compared. The unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 46 publications
(39 reference statements)
2
26
1
Order By: Relevance
“…Moua et al have observed that in non-IPF patients, an AE-ILD did not cause increased mortality in comparison with other types of hospitalizations in a multivariate model [5]. These ndings may re ect the fact that AE-ILDs are less fatal for non-IPF patients than for those patients with IPF, which was also supported by our previous study, where IPF patients had a signi cantly shorter survival after an AE in comparison with non-IPF patients [14].…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Moua et al have observed that in non-IPF patients, an AE-ILD did not cause increased mortality in comparison with other types of hospitalizations in a multivariate model [5]. These ndings may re ect the fact that AE-ILDs are less fatal for non-IPF patients than for those patients with IPF, which was also supported by our previous study, where IPF patients had a signi cantly shorter survival after an AE in comparison with non-IPF patients [14].…”
Section: Discussionsupporting
confidence: 82%
“…The study material consists of ILD patients who were non-electively hospitalized due to acute respiratory symptoms in OUH or OH between 1/1/2008 and 31/12/2017. A total of 128 of these patients were also included in our previous study [14]. The owchart of the study and criteria used to de ne AE-ILD are presented in Fig.…”
Section: Patient and Data Collectionmentioning
confidence: 99%
See 3 more Smart Citations